PENGGUNAAN BAHASA BAGI KELOMPOK IMIGRAN DI MAKASSAR: SUATU KAJIAN KONTAK BAHASA - Andi Samsu Rijal; Andi Mega Januarti Putri; Sulviana - Sulviana; Andi Asdar (Universitas Sarjanawiyata Tamansiswa, 2020)
Language contact is a verbal communication interaction at the same place and time. The phenomenon of language contact can be found in the city of Makassar, both the people of South Sulawesi themselves and immigrant groups from various Middle Eastern countries, where the city of Makassar is used as a temporary area before visiting the destination countries, namely Australia, Canada and America. Seeing the volume of immigrants from 2014 to 2019 living in Makassar, of course every day they interact with the people of Makassar City. The purpose of this article is to describe the use of language for immigrants in interacting with the people of Makassar. The method used is the method of observation and interviews. From the observations it was found that the use of English was only used to interact formally both to UNHCR officers, IOM staff, and to Makassar residents who greeted them in English, Indonesian was also used formally, but in daily interactions a variation of Makassar Malay was used ( BMM) such as when buying, selling, exercising, and other social adaptations. The use of BMM indicates that it is an adaptation effort for language and culture made by immigrant groups to be socially accepted in the Makassar city environment.